Heat Source/Sink on MHD Flow of Dusty Nano fluid over a Stretching Surface with Volume Fraction of Dust Particle - Zaimuddin, Izzatun Nazurah; Kandasamy, Ramasamy; Aman, Fazlina (INSTITUTE OF ADVANCED SCIENTIFIC RESEARCH, 2020)
The presence of the non-uniform heat source/sink of MHD nanofluid have been investigated numerically which resulted from a past stretching surface. The model includes the effects of parameter such as heat source/sink, volume fraction of dust particles, magnetic field, mass concentration of dust particles, fluid particle interaction and porosity effects. The basic governing of partial differential equations of the flow and heat transfer have been reduced to a set of nonlinear ordinary differential equations by using steady state flow in similarity transformation and then solved analytically using shooting technique. Various physical parameters’ effects on velocity and temperature profiles of the flow are discussed and presented through graphs in details. Numerical results obtained are verified by comparing the present study with the existed study. The result of the present study proves to be highly satisfactory.